Pengaruh Penerapan Teknologi Video Feedbcak dalam Meningkatkan Dasar Passing Sepak Bola SSB Merpati Cerih - Muhammad Zidan Aldar; Dedi Iskandar (Lembaga Pengembangan Kinerja Dosen, 2025)
Passing is a fundamental skill that is crucial in soccer because it plays a role in maintaining ball possession, controlling tempo, and creating scoring opportunities. However, in practice, many young players still struggle to pass correctly, both in terms of foot technique, strength, and accuracy of the ball's direction. Technological advancements in the world of sports offer various learning alternatives, one of which is through video feedback. This technology allows players to review their movements, making it easier to identify technical errors and make systematic improvements. Therefore, this study was conducted to determine the effect of video feedback on improving passing skills in young players. This study used an experimental method with a one-group pretest-posttest design. The subjects were 20 SSB Merpati Cerih U-14 players selected using a total sampling technique. The research instrument was a passing skills test administered before and after treatment. The test data were analyzed using descriptive and inferential statistics to measure the difference in average passing skill scores before and after the video feedback application. The results showed a significant improvement in passing ability after players received video feedback training. Players were able to correct technical errors, such as body position, leg swing, and pass direction. Visualizing movements directly through video recordings helps players more quickly identify weaknesses and correct them in subsequent training sessions. In conclusion, the application of video feedback technology has proven effective in improving basic passing skills in SSB Merpati Cerih U-14 players. This approach makes the learning process more interactive, motivates players, and optimizes training results. The application of similar technology is highly relevant to support achievement development in youth soccer.